Effects of three weeks of intensified training and two weeks of taper on mitochondrial respiration in humans - Granata, C. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Mitochondrial respiration has been reported to be an important determinant of endurance performance [1], and interval training (IT) has been shown to induce increases in maximal ADP-stimulated mitochondrial respiration [2]. Despite this, little is known about the effects of a period of intensified training on mitochondrial respiration. Furthermore, to our knowledge, the effects of reduced training workload (i.e., taper) on mitochondrial respiration have not been reported to date. Hence, the purpose of our study was to measure mitochondrial respiration following intensified training and taper, and to determine if changes were associated with changes in cycling performance (20-km time trial). Methods: Ten active men (VO2Peak= 47.0 mL/min/kg) took part in an intensified cycling training program (INT), performing an IT protocol twice a day for twenty consecutive days, followed by a two-week exponential taper (TP) consisting of 6 training sessions. Carbohydrate supplementation was used in order to prevent overreaching during the INT phase [3]. Muscle biopsies were taken from the vastus lateralis muscle before the study and after the INT and TP phases. Maximal (5 mM ADP) ADP-stimulated mitochondrial respiration was determined on permeabilised muscle fibers. Results: Maximal ADP-stimulated and non-coupled respiration simultaneously increased and decreased significantly during the INT and TP phase, respectively. Interestingly ADP sensitivity (0.25 and 0.5 mM ADP) showed no significant change during either phase. Finally complex IV reserve respiration increased significantly but to a lesser extent than maximal respiration during INT and dropped below initial levels after TP. The changes in maximal respiration tended to mirror performance changes. Discussion: Our study demonstrates that three weeks of INT increased maximal and non-coupled mitochondrial respiration by 30 and 40% respectively, and this was associated with a 5% increase in 20-km TT performance. Surprisingly, the exponential TP resulted in a non-significant decrease in performance; this was accompanied by a marked decrease in maximal respiration (15%), underlining the remarkable plasticity of skeletal muscle oxidative capacity.